The Loanwords from Eastern Slavic Languages in M. Petkevičius’s Catechism (1598): Criteria of Source Availability and Phonological Analysis - Smetonienė, Anželika (Lietuvių kalba, 2025)
The Catechism by Merkelis Petkevičius’ (hereinafter - PC), published in 1598, i.e. only three years after the first book in Lithuanian in the Grand Duchy of Lithuania, has been relatively scarcely researched up to now. J. Kruopas, who contributed most to the research on M. Petkevičius’ Catechism, compiled a dictionary of PC. The goal of J. Kruopas was not to investigate the origin of the borrowed words in PC; however, the origin of foreign words is noted. For the same reason, the origin of the loanwords is not argued, and the sources of the loanwords are not provided. This article aims to identify loanwords in the PC that came from Eastern Slavic languages, such as Ruthenian or Old Russian, and to present them together with their exact equivalents in the donor languages. To achieve this goal, all words with an obviously borrowed root were selected from M. Petkevičius’ Catechism. The examined words are generalised, i.e., prefix-derived words are not counted if the meaning of the word is modified only by the prefix. The collected words were compared with words in Slavic languages, based on dictionaries of Slavic languages from the relevant period, in order to find possible equivalents. Based on various criteria for determining the origin of loanwords, Slavisms, Polonisms, and loanwords from the East Slavic language group of uncertain origin were identified. This article presents those loanwords from Ruthenian or Old Russian whose origin is certain or subject to minimal doubt. The origin of the loanwords presented in the article has been determined based on several criteria that quite reliably indicate the donor language of the loanword. In general, the exact origin of a Slavic loanword can be determined when only one Slavic language (only Polish or only Ruthenian, Old Russian) attests to the possible source of the loanword (the criterion of available equivalents). Another informative criterion involves various phonological processes in Slavic languages and Lithuanian. The latter criterion covers a relatively large number of phenomena, and on this basis, 68 loanwords have been identified that came into the Lithuanian language from Ruthenian or Old Russian. Based on the criterion of the existence of a source, only nine Slavisms have been identified.